Gefangen in Mauthausen Europa in Mauthausen. Geschichte der Überlebenden eines nationalsozialistischen Konzentrationslagers, Band 3 (Brill, 2024)
"Gefangen in Mauthausen" (Imprisoned in Mauthausen) is volume three of a "major European project on the history of the survivors" (Carlo Moos). It deals with the everyday life of the concentration camp inmates and their attempts to make use of what opportunities for survival even the terror system offered. Their death or survival depended largely on what racist, national, political or occupational tags the SS had assigned to them and on the circumstances and the date of their arrival in the camp. The twenty-one papers in this volume present a new assessment of the inmates' worlds of living and show how diverse the "prisoner society" was when seen through the microscope of oral history.